2012
DOI: 10.1016/j.bbrc.2012.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen inhibits cytochrome c redox cycling induced lipid peroxidation

Abstract: Cytochrome (cyt) c can uncouple from the respiratory chain following mitochondrial stress and catalyze lipid peroxidation. Accumulating evidence shows that this phenomenon impairs mitochondrial respiratory function and also initiates the apoptotic cascade. Therefore, under certain conditions a pharmacological approach that can inhibit cyt c catalyzed lipid peroxidation may be beneficial. We recently showed that acetaminophen (ApAP) at normal pharmacologic concentrations can prevent hemoprotein-catalyzed lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Increased proton leaks lead to enhanced state 4 oxygen consumption, indicating a compensatory increase in electron transfer which is however associated with the increased “electron leakage” from the electron transport chain to oxygen producing superoxide (Dikalova et al , 2010). ApAP improves cardiolipin composition and reduces cardiolipin oxidation (Yin et al, 2012), which reduces proton leaks and results in improved respiratory control ratio and diminished electron leakage to superoxide formation (Dikalova et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased proton leaks lead to enhanced state 4 oxygen consumption, indicating a compensatory increase in electron transfer which is however associated with the increased “electron leakage” from the electron transport chain to oxygen producing superoxide (Dikalova et al , 2010). ApAP improves cardiolipin composition and reduces cardiolipin oxidation (Yin et al, 2012), which reduces proton leaks and results in improved respiratory control ratio and diminished electron leakage to superoxide formation (Dikalova et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cardiolipin content was performed as previously described (Yin et al , 2012). Briefly, lipids were extracted from 6 × 10 6 cells by addition of 0.75% NaCl and chloroform:methanol (2:1, v:v) containing 0.1 mM butyrated hydroxytoluene, 0.1 mM triphenylphosphine, and 2.5 μg tetramyristeoyl-cardiolipin (M 4 CL) as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is debate on the mechanism(s) of Cyt c release by mitochondria, it is well accepted that CL plays an important role in this process , and recent works showed that Cyt c can open nanoscale pores and cross through CL‐containing membranes . On these grounds, the modulation of Cyt c interaction with CL and identification of potential inhibitors of CL‐induced peroxidase activity have a priori a high relevance . Indeed, some of these inhibitors have shown anti‐apoptotic and neuroprotective actions in cellular and animal models of acute injury .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we observed dose-dependent inhibition of CL oxidation and formation of EAA-CL by a widely used analgesic drug acetaminophen (ApAP) that also served as a peroxidase inhibitor [15]. Furthermore, the very mechanism appeared to operate in vivo in the settings of atherosclerosis in a mice model of Western diet-induced atherosclerosis using low density lipoprotein receptor knockout (LDLR −/−) mice.…”
Section: Introductionmentioning
confidence: 99%